An observational comparative study of clinical efficacy and safety of chlordiazepoxide and lorazepam in alcohol withdrawal syndrome - D Tank, Nitishkumar; N. Karelia, Bharti; B. Bhansali, Nishant (International Journal of Medical Research and Review, 2016)
Background: Currently, Benzodiazepines like chlordiazepoxide, diazepam and lorazepam are the preferred drugs in the management of Alcohol withdrawal syndrome (AWS). These drugs of similar class are different in their pharmacokinetic profile which differently affect in AWS. Chlordiazepoxide is longer acting and converted to active metabolites in the liver, while lorazepam is shorter acting, with no active metabolites. Materials and methods: An observational, prospective and comparative study conducted in 100 patients of AWS. They received either Chlordiazepoxide or Lorazepam and divided into two comparison groups at the screening. Observation was started from day of admission to every day till day of discharge. The initial withdrawal assessment and subsequent changes in withdrawal during treatment were assessed using the Clinical Institute Withdrawal Assessment for Alcohol scale, revised (CIWA-Ar) in both the groups. Clinical global impression (CGI) score was also used to evaluate drug efficacy in both the groups. Details of adverse drug reactions, if any appear were recorded. Results: CIWA-Ar score, CGI-Severity (CGI-S) score and CGI-Improvement (CGI-I) score showed statistically significant difference between two groups. But percentage reduction in CIWA-Ar, CGI-S and CGI-I score were almost similar in both groups. Intra group comparison at different duration of treatment progressed and in between days of treatment there was statistically significant reduction of these scores. Considering no. of adverse events, reported adverse events causality, severity, predictability and preventability assessment, both drugs were safe. Conclusion: Both the drugs had almost similar efficacy in terms of to reduce CIWA-Ar score, CGI-S score, CGI-I score and similar safety profile.